(untitled) (The Review of Diabetic Studies, 2025)
Acute myocardial infarction (AMI) is a leading cause of mortality worldwide, where time-sensitive intervention remains the single most critical determinant of survival. Paramedics serve as the first line of medical response and play a pivotal role in identifying AMI, initiating early treatment, and expediting reperfusion strategies before hospital arrival. This systematic review critically examines the effectiveness of paramedic-led pre-hospital interventions, including electrocardiogram (ECG) acquisition and transmission, pre-hospital thrombolysis, administration of antiplatelet agents, pain management, and activation of catheterization laboratories. Using data extracted from peer-reviewed studies published between 2015 and 2024, this review evaluates the impact of these interventions on treatment delays, mortality rates, myocardial salvage, and patient outcomes. Findings indicate that early paramedic intervention significantly reduces door-to-balloon time, increases the likelihood of reperfusion within the critical “golden hour,” and improves both short-term and long-term clinical outcomes. Moreover, integration of telemedicine and advanced life support (ALS) training enhances diagnostic accuracy and decision-making efficiency in pre-hospital settings. The review concludes that paramedic-led strategies are essential for optimizing emergency cardiac care pathways and recommends further investment in training, technology, and standardized protocols to maximize clinical benefits.